A Compact Violin-Shaped Monopole Antenna for Ultra-Wideband Applications - Alwan, Younes S.; Zidan, Mohammad S.; Ibrahim, Omar J. (IAES Indonesian Section, 2024)
A case study of a miniature monopole planar fiddle or violin-shaped antenna that can be used in ultra-wideband (UWB) application is carried out. Such violin-shaped antenna is a circular patch accompanied with two circular cuts and overlapped with an elliptical patch on the top of it. It is small in size, simple in structure, feasible to construct and experimentally feasible to be manufactured and validated in lab. Furthermore, the handle of the fiddlelike structure serves as a microstrip 50? feeding line connected to the main patch structure body. However, the prototype of the designed antenna is manufactured on a substrate of a dielectric material of FR4 with a dielectric constant that equals 4.3 with dimensions of 28×18×1.6 mm3. The gain at the resonant frequencies reached different values throughout the covered frequency band; that is of (3.1 GHz up to 13.5 GHz) ranging between the values of (≈1.1 dBi up to ≈5.5 dBi) according to the return loss of the performance outcome. The empirically measured and simulated results have a suitable settlement and/or agreement and computations display that the antenna has a respectable frequency band, radiation, and characteristics of time domain in spite of the antenna’s small size and simple design.